Chemical composition and antioxidant activity of extracts from Bidens pilosa flowers - Lê, Lâm Sơn; Lê, Trung Hiếu; Nguyễn, Quang Mẫn; Hồ, Xuân Anh Vũ; Trần , Thanh Minh; Nguyễn, Việt Thắng; Nguyễn Đăng, Giáng Châu; Lê , Thuỳ Trang; Lê Thị, Mỹ Linh; Trần Thị, Văn Thi (Hue University Journal of Science: Natural Science, 2022)
Bidens pilosa is used in traditional medicine in Vietnam. The antioxidant potential of the ethanol extract and fractions from the flowers of Bidens pilosa was evaluated through DPPH and ABTS radical scavenging and the total antioxidant capacity method. The ethyl acetate fraction exhibits the highest activity with the lowest IC50 value (IC50 = 31.54 μg·mL–1 and IC50 = 35.33 μg·mL–1 for DPPH and ABTS radical scavenging capacity), and the total antioxidant capacity was 85.05 ± 0.28 mg GA·g–1. The composition of Bidens pilosa flowers: the total phenolic, total flavonoid, polysaccharides, and triterpenoid, was examined by using the colorimetric method, and their quantities are equivalent to 59.35 ± 0.83 mg GAE·g–1, 42.35 ± 1.50 mg QE·g–1, 4.44 ± 0.02%, and 32.88 ± 0.66 mg acid oleanolic·g–1, respectively. Specifically, the polysaccharide and total triterpenoid content of Bidens pilosa flowers was reported for the first time.